Anisotropic Field-of-View support for Golden Angle Radial Imaging - Wu, Ziyue (Magn Reson Med, 2015)
PURPOSE: To provide anisotropic field-of-view (FOV) support for golden angle radial imaging. THEORY AND METHODS: In radial imaging, uniform spoke density leads to a circular FOV, which is excessive for objects with anisotropic dimensions. Larson et al. previously showed that the angular k-space spoke density can be determined by the desired anisotropic FOV. We show that conventional golden angle sampling can be deployed in an angle-normalized space and transformed back to k-space such that the desired non-uniform spoke density is preserved for arbitrary temporal window length. Elliptical FOVs were used to illustrate this generalized mapping approach. Point-spread-function and spoke density analysis was performed. Phantom and in vivo cardiac images were acquired. RESULTS: Simulations, phantom, and in vivo experiments confirmed that the proposed method is able to achieve anisotropic FOV while still maintaining the benefits of golden angle sampling. This approach requires 50% less spokes for elliptical FOV with major-to-minor-axis ratio of 1:0.3, when compared to isotropic FOV with the same undersampling factor. CONCLUSIONS: We demonstrate a simple method for applying golden angle view ordering to anisotropic FOV radial imaging. This can reduce imaging time for objects with anisotropic dimensions while still allowing arbitrary temporal window selection.